Appraisal of heavy metal toxicity in surface water with human health risk by a novel approach: a study on an urban river in vicinity to industrial areas of Bangladesh. (2nd October 2021) - Proshad, Ram; Islam, Saiful; Tusher, Tanmoy Roy; Zhang, Dan; Khadka, Sujan; Gao, Jianing; Kundu, Satyajit
Abstract: Water quality is a big concern for the humankind as it is the most important natural resource. Water is polluted by increasing activities of population and the necessity to provide them with goods and services that use water as a vital resource. In this study, surface water samples were collected in the summer and the winter season from Rupsa river, Bangladesh, and pH, electrical conductivity (EC), Cr, Ni, Cu, As, Cd and Pb concentrations were analyzed to assess the metal toxicity, identify the possible sources and determine health risk from metals in water. During the the summer season, the mean concentrations of Cr, Pb, As, Cu, Ni and Cd were measured as 7.20 ± 0.613, 7.09 ± 0.904, 5.45 ± 0.441, 5.36 ± 0.471, 3.85 ± 0.694 and 0.975 ± 0.106 µg/L, respectively, whereas the concentrations were measured as 8.87 ± 0.756, 7.32 ± 0.93, 6.05 ± 0.490, 6.02 ± 0.529, 5.48 ± 0.986 and 1.38 ± 0.151 µg/L, respectively, during the the winter season. Source identification like correlation analysis, Principal component analysis (PCA) and cluster analysis (CA) were applied to identify the source of toxic metals in water. Total heavy metal toxicity load and heavy metal evaluation index values were found to be higher than permissible value except for Cu. According to the ecological risk index classification, 85% of the total samples were found to pose moderate ecological risks, while the rest 15% were found to pose low ecological risks during both seasons. As showed high non-carcinogenic risk on the basis of single element via oral exposure. The hazard index value for oral exposure by male, female and children was found to be 4.17E + 00, 3.67E + 00 and 8.64E + 00, respectively; indicating that non-carcinogenic effects are obvious to occur. The carcinogenic risks of Ni and As due to regular exposure via oral and dermal contact pathways were higher than the standard value (>1.0E-04) which anticipated possible cancer risks to male, female and children in the study area.